O último a sair apague a luz: a economia comportamental aplicada ao consumo de energia elétrica da UFG - Jesus, Wesdra Xavier de (2018)
This study brings theoretical levers of Behavioral Economics applied to the public sector. The Federal University of Goiás, faced with its expansion in recent years, driven by growth programs, faced with the need to adjust its budgetary reality to the frank expansion of its funding, among them, electric energy that is treated in this research. The institution made use of tools of the Behavioral Economics with the use of nudges in order to seek to circumvent resource allocation needs beyond and behavioral changes of its population for saving of electric energy, being the analysis of this action the objective of the research. The methodology used was to search among the Consumer Units randomly, within some established basic prerequisites, those that served as the basis for comparative mathematical calculations related to assessing the efficiency, effectiveness and effectiveness of the action. The results showed that within what was established by the action, among the Consumer Units tested, the results were within the expected by the action. The intervention proposal was the recommendation of the use of a manual for insertion of nudges, besides proposing other forms of nudge use, and it is suggested to use virtual banners on the institution's internet pages